Strengthening Nutrition Literacy and Scientific Skills through Multisensory Food Experience among Children at Al-Faruq Kindergarten in Kawahmanuk Village, Kuningan Regency - Teti Nurhayati; Daesylina Daesylina; Edi Waluyo; Ali Forman (Yayasan Darussalam Bengkulu, 2026)
Nutrition literacy in early childhood should not be reduced to the memorisation of healthy and unhealthy foods; it should be developed through concrete, sensory, affective, and socially supported experiences that help children observe, classify, communicate, and make simple food-related decisions. This study aims to describe how multisensory food experience learning contributes to nutrition literacy and basic science process skills among children aged 5-6 years. A descriptive qualitative design was implemented at Al-Faruq Kindergarten, Kawahmanuk Village, Kuningan Regency, West Java, over eight weekly sessions from February 2 to March 30, 2026. Participants consisted of 15 children, two classroom teachers, and eight parents. Data were collected through participant observation, semi-structured interviews, children’s work, teacher reflection notes, and activity documentation. The data were analysed through data condensation, thematic display, and conclusion verification, supported by source and method triangulation. The findings reveal four interrelated themes: improved nutrition understanding through sensory engagement, more positive emotional responses and willingness to try healthy foods, the emergence of simple healthy lifestyle practices, and the decisive role of school-family collaboration. The activities also stimulated basic science process skills, especially observation, classification, comparison, causal explanation, and communication. The study contributes a context-based pedagogical model that integrates early childhood science education, nutrition literacy, and health education through experiential and multisensory learning. Because the study is qualitative, single-site, and short-term, the findings should be interpreted as process evidence rather than causal effectiveness evidence.